Eu que me invento outro: um estudo do livro Escritura da palavra e do som - de Paulo Garcez de Sena - Silva, Ricardo Emanuel Lago e (2014)
In this work, we study the aspect metapoético intertextuality and the book of Scripture word & sound, (1985) the Bahian poet Paulo Augusto Garcez Sena, (1942-1998). We proceed to a preliminary contextualization of the author, standing cultural and historical environment in which he lived and produced his work. Then work the issue of intertextuality in metapoetry and only book published by the author, considering the themes of making poetry itself, the muses and intertextual dialogue. To this end, we resort to a theoretical tool consisting of Jung, Campbell, Bachelard, Durand, Barthes, and Octavio Paz and theories of Bakhtin carnivalization in literature. It is postulated that the poetry of Paulo Augusto Sena presents Garcez tune with contemporary production in some of its most representative aspects.